Pengikatan Jaminan Pesawat Udara Terkait Dengan Ratifikasi Konvensi Cape Town 2001 Untuk Kepentingan Penerbangan Internasional - Nanda Dwi Rizkia; Yuhelson; Ramlani Lina S (Jurnal Hukum Sasana, 2021)
Exorbitant price of an airplane in Indonesia makes it inconvenient for domestic commercial airline companies to buy it in cash, therefore these airline companies need some firm bank and non-bank financial institutions for financial arrangement with a purpose of providing them credit payment with lease agreements, a venture with no option rights are unlikely found by bank or domestic financial institutions that responsible as creditor or lessor because aside from the excessive number of loans, the risk of default is high as well. Normative juridical research method, is a process to find the regulations, principles and doctrines of law in order to response and faced any legal issues, the outcome of research is domestic airlines inclined to choose leasing companies from abroad to get foreign creditors, the government of Indonesia has ratified the 2001 Cape Town Convention with the issuance of Law No. 1 of 2009 concerning Aviation which makes it easier for domestic commercial airlines to procure airplane under the SGU agreement because foreign creditors get legal warranty that have been acknowledged internationally. The convention regulates the creditor or the lessor of the airplane can withdraw directly from the debtor and operate the airplane as a leasing object without any options rights and procedures.